The development and integration of smart curtain and alarm clock / Zuhayra Nasrin Zainudin - Zainudin, Zuhayra Nasrin (2018)
Everyone has different sleep personality. With a proven statistic, people still having problem with waking even with the help of alarm clock. Not only that, the use of Smart Automation has been widely used as the evolution of technology is increasing. In this project, it’s specifically indicates toward heavy sleepers who might have problem with waking on time; moreover, this project helps to lessen chores by using the curtain automation. With some references from previous projects of Smart Curtain automation and Digital alarm clock, many solutions has been come out to evolving this new technology, furthermore, there are new features that have been added to make a difference between this new project with the existing one. After all, consideration of technology used to create this new device still accommodate with nowadays lifestyle.